Effect of economic growth on CO2 emission in developing countries: Evidence from a dynamic panel threshold model - Goodness C. Aye; Prosper Ebruvwiyo Edoja (Cogent Economics & Finance, 2017)
This study investigated the effect of economic growth on CO2 emission using the dynamic panel threshold framework. The analysis is based on data from a panel of 31 developing countries. The results indicate that economic growth has negative effect on CO2 emission in the low growth regime but positive effect in the high growth regime with the marginal effect being higher in the high growth regime. Thus our finding provides no support for the Environmental Kuznets Curve (EKC) hypothesis; rather a U-shaped relationship is established. Energy consumption and population were also found to exert positive and significant effect on CO2 emission. Including financial development indicator in the model did not change the conclusion about EKC hypothesis. Employing panel causality methods, there is evidence of significant causal relationship between CO2 emission, economic growth, energy consumption and financial development. The findings emphasize the need for transformation of low carbon technologies aimed at reducing emissions and sustainable economic growth. This may include energy efficiency and switch away from non-renewable energy to renewable energy.
Keywords: 330; CO2 emission; economic growth; energy consumption; population; dynamic panel threshold model; panel causality